AN INNOVATIVE APPROACH TO MATHEMATICS EDUCATION - Adilya Kadyrova Rashidovna; Nigora Islomova Hamzayevna (American Journals Publishing, 2022)
Nowadays, improving the quality of education, students' deep mastery of mathematics and natural sciences has become the main task in our Republic. In order to increase students' interest in mathematics, it is necessary to increase their knowledge first. In order to increase students' knowledge, it is necessary to pay great attention to independent work and creative thinking of students in mathematics classes.
Keywords: improving the quality of education, mathematics, increasing interest and knowledge, independent work and creative thinking, development of the Motherland.